Kegiatan Relawan Pajak dalam Pelaporan Surat Pemberitahuan Tahunan dan Pemadanan NIK-NPWP di KP2KP Bengkayang - Sasmitha, Dian; Beni, Sabinus (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Tax Volunteers are one of the govemment programa, especially the Directorate General of Taxes, which aims to increase tax inclusion and awareness of taxes in the community around Bengkayang Regency. The Shanti Bhuana Institute carries out tax center management recruitment for Shanti Bhuana Institute students who will become prospective tax volunteers, then interviewa and writing tests are carried out. The regionl office will inaugurate tax volunteers who pass the selection. These tax volunteers will help KP2KP in Bengkayang to help increase awareness of texpayers to always report tax obligations and help in filing out and reporting annual SPT a based-on e – filling. Apart from that, tax volunteer willalso help carry out socialization and assistance to taxpayers in watching NIK-NPWP